Frank Lloyd Wright's Fallingwater [videorecording] - Waggoner, Lynda S.; Cleary, Sarah; Sakamoto, Timothy; Park, Dennis; In-D (Firm); Western Pennsylvania Conservancy (Los Angeles, Calif. : In-D Press, 2005)
This virtual tour of Fallingwater, a home Wright designed over a stream in the Pennsylvania mountains in 1935, illustrates and explores his concept of "organic" architecture, integrating a building, its site and its inhabitants into a unified whole